2014
DOI: 10.1016/j.pjnns.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of Virchow–Robin spaces in children hospitalized at pediatric neurology department

Abstract: Higher incidence of dVRs was found in children with headache and epilepsy. No association was found between localization of dVRs and symptomatology of different nervous system diseases except for large dVRs probably due to the pressure on the surrounding tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
2
18
2
1
Order By: Relevance
“…Three studies investigated PVS among children and the fourth among adults as well. Two studies (1,2) found a positive association between migraine and PVS, the third (3) between headache and PVS and the fourth (4) between both headache and migraine and PVS. Since migraine may be associated with neurogenic perivascular inflammation (5) and PVS are linked to lymphatic drainage of the brain parenchyma (6), it seems plausible that migraine could increase the number of PVS visible on MRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated PVS among children and the fourth among adults as well. Two studies (1,2) found a positive association between migraine and PVS, the third (3) between headache and PVS and the fourth (4) between both headache and migraine and PVS. Since migraine may be associated with neurogenic perivascular inflammation (5) and PVS are linked to lymphatic drainage of the brain parenchyma (6), it seems plausible that migraine could increase the number of PVS visible on MRI.…”
Section: Introductionmentioning
confidence: 99%
“…This study included PVS in BG and HWM. Three of the previous studies investigated only PVS in the HWM (13) whereas the fourth investigated both BG and HWM (4).
Figure 1.Perivascular spaces (PVS) in the hemispheric white (HWM) matter visible on magnetic resonance imaging (MRI).
…”
Section: Introductionmentioning
confidence: 99%
“…Changes in white matter are associated with aging and hypertension [25], [26]. White matter changes are foci of gliosis and ischemic demyelination [27]. We classified pineal cysts as minor abnormalities except when present with mass effect leading to compression of the superior colliculus or compression on cerebral aqueduct and cause an obstructive hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…20 Nonspecific white matter abnormalities are foci of ischemic demyelination and gliosis. 26 These abnormalities are detected best as hyperintense foci on T2-weighted sequences. In this study, nonspecific white matter abnormalities were found in 42 of 127 (10%) patients who underwent brain MRI.…”
Section: Discussionmentioning
confidence: 99%